The Effect of a Training Program for the Innovation and Imagination skills of Students of the Institute of Fine Arts in the Subject of Innovation and Mime (Journal of the College of Basic Education, 2023)
The current research aimed to develop the creativity and imagination skills of the students of the Institute of Fine Arts in the subject of innovation and silence. The researcher adopted the experimental approach and adopted a research tool (observation form) of her design and found it to be honest and reliable.